KONSEP DAN IMPLEMENTASI ETIKA ISLAM DALAM DUNIA BISNIS - Nurul Fatima Hasan (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2017)
Indeed, in terms of the whole implementation of life has been arranged in the view of Islamic teachings to regulate all human life including in relation to the implementation of the economy and business. Islam does not allow any person to work haphazardly to achieve his/her goals and desires by justifying any means such as committing fraud, cheating, false vows, usury, and any other vanity deeds. But, Islam has given a boundary or line between the allowable and the unlawful, the right and wrong and the lawful and the unlawful. These limits or dividing lines are known as ethics. Behavior in business or trade is also not escaped from the moral value or business ethics values. Islamic business ethics is of which adheres to the principle of unity, equilibrium principle, freewill principle, responsibility principle, It is important for business people to integrate that ethical dimension into the framework or scope of the business.